Mechanistic Divergence in the Hydrogenative Synthesis of Furans and Butenolides: Ruthenium Carbenes Formed by gem‐Hydrogenation or through Carbophilic Activation of Alkynes. Issue 51 (6th November 2019) - Peil, Sebastian; Fürstner, Alois
Abstract: Enynes with a tethered carbonyl substituent are converted into substituted furan derivatives upon hydrogenation using [Cp*RuCl]4 as the catalyst. Paradoxically, this transformation can occur along two distinct pathways, each of which proceeds via discrete pianostool ruthenium carbenes. In the first case, hydrogenation and carbene formation are synchronized ("gem‐hydrogenation"), whereas the second pathway comprises carbene formation by carbophilic activation of the triple bond, followed by hydrogenative catalyst recycling. Representative carbene intermediates of either route were characterized by X‐ray crystallography; the structural data prove that the attack of the carbonyl group on the electrophilic carbene center follows a Bürgi–Dunitz trajectory. Abstract : One way or the other : Enynes bearing a tethered carbonyl group are transformed into furans upon catalytic hydrogenation using a ruthenium catalyst. Strikingly though, the reaction can follow two distinct pathways, each of which involves discrete metal carbene intermediates. They differ in that the hydrogenation and carbene formation are either synchronized ( gem ‐hydrogenation) or fully uncoupled.